FORMULASI SEDIAAN OBAT KUMUR KOMBINASI EKSTRAK DAUN GAMBIR (Uncraina gambir (Hunter) Roxb) dan BIJI PINANG (Areca catechu L.) SEBAGAI ANTIBAKTERI - Dini Mardhiyani (Universitas Cokroaminoto Palopo, 2023)
Bad breath (Halitosis) is one of the oral health problems that many people complain about after caries and periodontal disease. Plants that have the potential to be used as mouthwash preparations are gambier leaves and areca nut seeds. The content of phenol and catechin compounds has the ability as a bactericidal. Meanwhile, areca nut has the ability to inhibit the release of calcium ions in the tooth demineralization process stimulated by Streptococcus mutans. This study aims to determine the evaluation results of a combination of gambier leaf and areca nut mouthwash preparations with concentrations of 0.5%, 1%, and 1.5% with several physical parameters, namely organoleptic tests, pH tests, clarity tests, and viscosity tests. Physical stability testing was carried out on Day 0 and Day 7. The results of the organoleptic test are liquid, odorless, white and yellowish brown, sweet and bitter taste. ptest day 0 on controls, F1, F2, and F3, namely 6.2, 4.8, 4.8, 4.6, and day 7 on controls, F1, F2, and F3, namely 6.2, 4 ,7, 4,6, 4,4. Clarity test on day 0 and day 7 controls, F1, F2, and F3 were clear. Viscosity test day 0 on controls, F1, F2, and F3, namely 11.40 cPoises, 9.88 cPoises, 7,271 cPoises, 10.13 cPoises and day 7 on controls, F1, F2, and F3, namely 7,725 cPoises, 9,380 cPoises, 10,218 cPoises, 11 cPoises.